Reliability and differentiation capability of dynamic and static kinematic measurements of rearfoot eversion in patellofemoral pain - Silva, Danilo de Oliveira; Briani, Ronaldo Valdir; Pazzinatto, Marcella Ferraz [UNESP]; Ferrari, Deisi; Aragão, Fernando Amâncio; Albuquerque, Carlos Eduardo de; Alves, Neri [UNESP]; Azevedo, Fábio Mícolis de [UNESP] (Elsevier B. V., 2015)
Excessive rearfoot eversion is thought to be a risk factor for patellofemoral pain development, due to the kinesiological relationship with ascendant adaptations. Individuals with patellofemoral pain are often diagnosed through static clinical tests, in scientific studies and clinical practice. However, the adaptations seem to appear in dynamic conditions. Performing static vs. dynamic evaluations of widely used measures would add to the knowledge in this area. Thus, the aim of this study was to determine the reliability and differentiation capability of three rearfoot eversion measures: rearfoot range of motion, static clinical test and static measurement using a three-dimensional system. A total of 29 individuals with patellofemoral pain and 25 control individuals (18-30 years) participated in this study. Each subject underwent three-dimensional motion analysis during stair climbing and static clinical tests. Intraclass correlation coefficient and standard error measurements were performed to verify the reliability of the variables and receiver operating characteristic curves to show the diagnostic accuracy of each variable. In addition, analyses of variance were performed to identify differences between groups. Rearfoot range of motion demonstrated higher diagnostic accuracy (an area under the curve score of 0.72) than static measures and was able to differentiate the groups. Only the static clinical test presented poor and moderate reliability. Other variables presented high to very high values. Rearfoot range of motion was the variable that presented the best results in terms of reliability and differentiation capability. Static variables do not seem to be related to patellofemoral pain and have low accuracy values.
Keywords: Anterior knee pain; Kinematics; Patellofemoral joint; Roc curves; Subtalar joint